Creative activity of primary school teachers in the conditions of distance learning - Сарсекулова, Диляра; Жолтаева , Гульнар; Майлыбаева , Гульмира; Ахметсапа , Айгүл (Pedagogy and Psychology, 2023)
In the article, in connection with the changes currently taking place in social and economic life, the urgency of the problem of formation of teachers' readiness for professional and creative activity in the conditions of distance learning is substantiated. Attention is drawn to the formation and development of creative abilities of students in the conditions of distance learning through the use of ICT and digital educational resources. Based on the analysis of theoretical research and educational practice, the principles of the development of creative abilities of students in the classroom are determined. The possibilities of the content of the educational program of primary school in the development of creative abilities of students in educational activities are shown. The types, brief characteristics of information and communication technologies and digital educational resources intended for the educational process of primary school, as well as their capabilities in the formation and development of creative abilities of students are described. There is also a sample of a short-term plan for an online math lesson, including creative work.